The Effect of Digital Transformation on University Brand Image with Ownership as a Moderating Variable - Julita, Julita; Helmi, Sulaiman; Gunarto, Muji; Sartika, Dewi (International Journal of Finance Research, 2024)
The digital era demands transformation from universities, including private ones. However, the effectiveness of digital transformation on university brand image can be strengthened by ownership. This research investigates the impact of digital transformation on the university's brand image, with ownership as a moderating variable. Using random sampling, we analyzed 45 private universities affiliated with Private Universities in Indonesia Region 2A. This exploratory study employed a quantitative method. The results indicate a significant positive relationship between digital transformation and university brand image, suggesting an enhancement of the university's reputation in the eyes of the public. However, the study also reveals that ownership does not mediate the relationship between digital transformation and university brand image. This suggests that each university may have different Ownership Competencies, especially in decision-making regarding digital transformation. The conclusion of this research indicates that digital transformation affects university brand image. However, specifically in the case of universities in LLDIKTI Region 2, ownership does not moderate the effects of digital transformation on university brand image. It is recommended that this research be continued using mixed methods to explore ownership moderation or test it in other regions' universities.